Identification of antibiotic use patterns in poultry farms in the southwest region of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2025)
The study was conducted in southwestern Bangladesh, 90 chicken farmers were surveyed across three upazilas under three districts of southwestern Bangladesh to understand the practices and farmers' perceptions of antibiotic use in poultry farming. Data were collected through direct interviews of poultry farmers using a pre-tested interview schedule. The results showed that the highest percentage of farmers kept broilers in their farms (30.0%), followed by layer (28.9%), Sonali (26.7%) and cockerel (14.4%). Farmers marketed broilers at an average of 35 days with a live weight of 2187.04 kg bird-1 and egg production of layer chickens was 88.88%. The majority of chicken farmers (84.44%) used antibiotics, while 47.8% and 92.2% of farmers used probiotics and vitamin-mineral supplements for chicken. The use of antibiotics was suggested by various people, such as veterinary doctors (35.56%), animal health workers (23.33%), drug company representatives (20.00%) and self (5.56%). More than half of the chicken farmers (56.67%) applied antibiotics regularly and the highest percentage was supplied through water (82.2%). Half of chicken farmers used antibiotics for disease prevention (50.00%), followed by treatment of sick chickens (31.11%), growth promotion (2.22%) and both disease prevention & growth promotion (1.11%). The majority of the farmers did not know about the negative impacts of antibiotic use in poultry farming (87.8%), among the remaining 7.8% of farmers said it was carcinogenic, 3.3% stated it was toxicity in humans and only 1.1% said it had no effect of antibiotics in human health. It can be concluded that most of the chicken farmers are using antibiotics indiscriminately, which suggests proper education and awareness creation of poultry farmers to reduce the risks associated with antibiotic use.Int. J. Agril. Res. Innov. Tech. 14(2): 1-8, December 2024